Сжатие изображений на основе компенсации контуров при вейвлет-преобразовании - Иванов, В.Г.; Любарский, М.Г.; Ломоносов, Ю.В. (Проблемы управления и информатики, 2006)
Пропонується новий метод стиснення, що полягає в багатомасштабному поділі зображення на контур і фон. Виділення контуру здійснюється в кожному масштабі на основі симетричного низькочастотного фільтру, а фон представлено вейвлеткоефіцієнтами. Показано, що даний метод порівняно з вейвлетпере- творенням є більш швидким і дозволяє одержати більш високий коефіцієнт стиснення зображення. The new method of compression consisting in multiscale separation of the map on a loop and a hum noise is offered. Selection of a loop is carried out in each scale on the basis of a symmetric lowfrequency filter, and the hum noise is represented by wavelet-factors. It is shown, that the given method, in comparison with wavelet conversion is faster and allows to receive higher aspect ratio of the map.